The Effect of Using Mind Mapping Technique towards Students’ Ability at Eleventh Grade of Senior High School Number 11 Jambi City - Maiharani, Windi Tri; Wennyta, Wennyta; Dewi, Kartika (JELT: Journal of English Language Teaching, 2023)
The aims of the research is to see whether using mind mapping techniques improves students' writing abilities. This research uses a quantitative approach with a quasi-experimental methodology. A pre-test and post-test are used to collect data in this design. This research took place at SMAN 11 Jambi City. The researcher used a simple random sampling strategy to select students for the sample. Students in XI MIPA 2 were taught using the mind mapping technique, while students in XI MIPA 1 were not. The data gathered for this research was analyzed using the SPSS application. To collect data, the researcher gave a writing exam, which consisted of writing an explanatory text. Students in the experimental class completed a writing test using a mind mapping technique, whereas students in the control class did not use a mind mapping technique. The data in this research is analyzed using normality, homogeneity, and t tests. The following are the research's findings: (1) Normality test results for the experimental class with sig. 0.752 > 0.05 and the control class with sig. 0.510 > 0.05 show that the research's normality test is normally distributed. (2) The homogeneity test findings of the experimental class with sig. 0.678 > 0.05 and the control class with sig. 0.457 > 0.05 in this research are homogeneous. (3) The t-test results for both classes with a sig. 0.000 0.05 indicate that using mind mapping techniques has an effect on students' writing results.